Qualidade de vida de idosos hipertensos em terapia medicamentosa - Ramos, Sigrid Shally Nascimento de Lyra (2017)
Introduction: Hypertension is a major public health problem and significant threat to the quality of life of the elderly hypertensive, in this way, it is important the studies those evaluate the quality of life of this population. Objective: To analyze the quality of life of elderly people with hypertension in use of drug therapy. Method: This is a descriptive research, cross-sectional study and quantitative approach, performed with 187 elderly people in a city of the microregion of the southern coast of Paraiba State. The project was approved by the Ethics Committee of the Federal University of Paraiba (CAAE: 50370415.8.0000.5188). The data collection took place between the months of March to May 2016, using a structured instrument covering sociodemographic and clinical variables, the test of Morisky-Green, and the Specific Questionnaire for Quality of Life Bulpitt and Fletcher's. The data were analyzed on the basis of measurements of distribution and central tendency, calculating Cronbach's alpha coefficient test, Pearson's chi-square test and binary logistic regression, compiled and structured in a database via the software Statistical Package for the Social Sciences, version 22.0. Results: Relating to sex, the feminine predominated (56.7%). There was a predominance of the age group between 60 and 70 years old (49.8%). The prevalence of marital status was married or consensual union (57.8%). How much schooling the prevalence was no year of study (80.2%). Referring to the individual monthly income prevailed to retirement and/or board (99.5%). On the subject of therapeutic adhesion (87, 17%) were adherents. As the variables associated with the loss in quality of life: peripheral vascular disease (93.9%), heart disease and kidney problems (100%); medicines: analgesics (100%) and antihypertensives (79.1%); life habits: smoking (89.5%) and alcohol (10%). Conclusion: On the basis of the above, it appears that the investigated hypertensive elderly showed significant damage in their quality of life.